PHONETICS IS A BRANCH OF LINGUISTICS - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
In languages in which tones are phonemic, the tone phonemes may be called tonemes . Though not all scholars working on such languages use these terms, they are by no means obsolete